DETERMINANTS OF REGIONAL FEATURES OF INTERACTION BETWEEN GOVERNMENT AND OPPOSITION - Стефурак, М. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article analyzes the historical, cultural, linguistic, socio-economic, religious, ideological and political factors that determine the relations between government and opposition.